Effectiveness of the Introduction Capital Market Activities to the Younger Generation Through the Support of Internship Programmes - Iman, Nurul; Nitawati, Elly Yuniar (PT FORMOSA CENDEKIA GLOBAL, 2024)
Stock trading on the capital market is one of the investment activities. The capital market has become one of the places where transactions on securities can be carried out. Given the importance of expertise in this field, there is an internship for students to apply the knowledge previously acquired from the Capital Market School. The highly expected output of the internship activity is that students are able to read stock price movements, where they understand when it is time to buy stocks and when it was time to sell stocks, to be able to make a profit. Participants who take part in this internship will have skills in Opening Stock Account Administration up to the release of RDN, Selling Buy Stock Practices, Analysis of Stock Price Movement Transaction Graphs, and Knowledge of Advanced Material for BPPE Certification.